Analyzing the Current Umbilical Cord-derived Mesenchymal Stem Cell Secretome Evidence for Erectile Dysfunction Management - Ria Margiana; Muhammad Fadhli Abdullah; Cennikon Pakpahan; Reny I'tishom; Supardi Supardi; Huriyah Adani Saoemi; Nguyen Hoai Bac (Wolters Kluwer - Medknow Publications, 2023)
Erectile dysfunction (ED) impacts millions of men, especially older men, and current treatment options, including tadalafil, phosphodiesterase type 5 inhibitors, and short-acting testosterone, are ineffective. This necessitates the immediate development of effective alternative ED treatments. In recent years, attention has been drawn to the secretome of umbilical cord-derived mesenchymal stem cells (UC-MSCs) due to its anti-inflammatory and immunomodulatory properties, which can reduce inflammation and promote tissue repair. The UC-MSCs secretome contains numerous growth factors, such as vascular endothelial growth factor, insulin-like growth factor 1 (IGF-1), and basic fibroblast growth factor (bFGF), which are essential for promoting endothelial cell proliferation and penile blood flow. This review seeks to examine the existing evidence on the use of stem cells, with a focus on UC-MSCs secretome, as a potential treatment modality for erectile dysfunction (ED). By reviewing the PubMed, Google Scholar, and Scopus databases, a comprehensive narrative review was conducted. Included among the search queries were "erectile dysfunction," "stem cells," "mesenchymal stem cells," "umbilical cord," and "secretome." Only research published in English within the past decade was included in the analysis. The findings indicate that the secretome of UC-MSCs has promise for treating ED. The secretome is composed of growth factors, cytokines, and other bioactive compounds that promote tissue repair and regeneration via paracrine effects on adjacent cells. The administration of UC-MSCs improved erectile function, penile blood flow, and smooth muscle content. In addition, discarded UC-MSCs serve as a cost-effective and copious source of ethically acceptable and immunogenic UC-MSCs with low immunogenicity. The secretome of UC-MSCs offers a potential therapeutic strategy for treating erectile dysfunction. However, further preclinical and clinical research must be done to determine the safety and efficacy of stem cell-based treatments for erectile dysfunction.